Addressing Critical Gaps in Health Workforce in Nepal’s Maternal Healthcare System: DOI: https://doi.org/10.46405/ejms.v6i9.519 - Paudel , Pravin; Amatya , Archana (Europasian Journal of Medical Sciences, 2024)
A nation’s capacity to achieve its health objectives relies heavily on the proficiency, dedication, and strategic deployment of the health workforce. Nepal’s efforts to address human resource challenges, particularly in maternal and child health, have experienced achievements and ongoing challenges. The country must continue to invest in comprehensive strategies that address geographical, economic, and educational disparities to improve healthcare service quality and accessibility. Enhancing the effectiveness of health systems goes beyond increasing the workforce size; it involves initiatives to evaluate and strengthen the health workforces’ recruitment, distribution, retention, and productivity. Strategies include exploring innovative approaches for pre-service and in-service training, implementing or refining incentives to address distribution and retention issues, and, when suitable, task-shifting—delegating tasks to less specialized health workers. The health workforce (human resources) is one of the six building blocks of a health system. In this commentary, we focus on the human resources aspect of the challenges in improving the health system in Nepal. In doing so, we draw upon the experiences of the Nick Simons Institute, an organization that has worked in Nepal for more than 15 years.4 The Institute’s primary mission has been to innovate solutions in rural healthcare by providing support to hospitals, training human resources, and advocating for enhancing the healthcare system in alignment with the Ministry of Health and Population (MoHP) in Nepal.